Coronary–Pulmonary Artery Fistula Ligation and Mitral Valve Repair Through a Mini-Thoracotomy Approach. Issue 3 (June 2019) - Kitahara, Hiroto; Tanaka, Chiharu; Nakanishi, Sentaro; Wakabayashi, Naohiro; Ishikawa, Natsuya; Kamiya, Hiroyuki
A 39-year-old man with severe mitral regurgitation was referred to our institution for surgical evaluation. During preoperative workup, a coronary–pulmonary artery fistula was incidentally found by computed tomography. After multidisciplinary cardiac team discussion, the decision was made to proceed with coronary–pulmonary artery fistula ligation and mitral valve repair through a mini-thoracotomy approach. Cardiopulmonary bypass was initiated with femoral vessels. A mini-thoracotomy was made in the fourth intercostal space. First, mitral valve repair with posterior leaflet folding and ring annuloplasty was done. The coronary–pulmonary artery fistula was running on the roof of the left atrium and was ligated with metal clips under thoracoscopic vision. Postoperative computed tomography showed no residual fistula.